Surgical treatment of non-unions in the ulna and radius: a one-year outcome study - Findeisen, Sebastian; Maier, Katinka; Ferbert, Thomas; Tanner, Michael Christopher; Großner, Tobias; Bewersdorf, Tim; Schamberger, Christian T.; Schmidmaier, Gerhard; Böpple, Jessica C. (European journal of trauma and emergency surgery, 2025)
The incidence of non-unions of the forearm following conservative or surgical treatment of forearm fractures ranges from 2% to 5.3%. These non-unions can lead to significant limitations in the patient’s physical capabilities, necessitating an appropriate treatment plan. The aim of this study was to evaluate osseous consolidation of forearm non-unions after six months and one year as well as to assess patient-reported outcomes. A total of 36 patients with non-unions of the forearm, operatively treated in our department between 01/10 and 12/21, completed the follow-up period for this study. Radiographic evaluation was performed using the modified Lane-Sandhu Score. Osseous consolidation was assessed at six and 12 months postoperatively. Additionally, patient-reported outcomes and variations of surgical treatment were analysed. The prevalence of non-unions in our study was 30.56% for the ulna, 50% for the radius, and 19.44% for both bones. 85% of patients received bone grafts, with 48% receiving cortico-cancellous bone grafts (CCBG) and 52% receiving cancellous bone from the iliac crest or femur. In total, 67% of patients demonstrated consolidation of the non-union within six months of surgical treatment, increasing to 89% after one year. Among patients who received CCBG, 86% showed consolidation at six months, rising to 100% at one year. Additionally, patient-reported outcome measures (PROMs), including VAS and SF-12 scores, showed overall improvement. A sufficiently long follow-up period is crucial for patients with forearm non-unions. To ensure consolidation, a follow-up period of at least six months to one year is recommended. Furthermore, the use of cortico-cancellous bone grafting combined with locking compression plates (LCP) appears to be an effective technique, providing stability during the healing process and achieving satisfactory bone healing one year postoperatively.
Online veröffentlicht: 25. November 2025
Gesehen am 23.01.2026